Capital Structure As Mediating Variable in Financial Performance and Good Corporate Governance Banking Sector - Kinasih, Lintang; Laeliyah, Evi Sofiatul; Neliana, Tri (Ann Publisher, 2025)
Background. Banking and financial institutions are essential to the functioning of modern economies, serving as key drivers of economic stability and growth. In Indonesia, the banking sector holds a dominant position within the financial system, playing a vital role in the implementation of monetary policy. Aims. Ensuring a robust banking environment depends on the practical application of GCG, which is assessed using the RGEC framework, consisting of Risk Profile, Governance, Earnings, and Capital. The importance of GCG has become even more evident following financial crises, such as the 1997 monetary crisis and the 2024 Bank BJB corruption scandal, both of which highlighted serious shortcomings in oversight and transparency. Methods. The population in this study comprises all banking companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. The sample was selected using purposive sampling, a method that involves selecting participants based on specific criteria to meet the study's objectives. The criteria applied included banks listed on the IDX and those that consistently published their financial statements from 2019 to 2023. Based on these criteria, a total of 51 banking companies were selected as the research sample Result. Although banking performance has improved, issues such as inefficiency and a lack of transparency persist. Studies indicate that GCG elements—such as board structure, audit committees, and ownership models—impact financial outcomes, though findings are not always consistent. Conclusion. This research examines the impact of GCG, incorporating capital structure as a mediating factor to gain a deeper understanding of these relationships. Focusing on the banking sector underscores its critical role in the economy and its ongoing digital transformation, reinforcing the need for governance systems that foster sustainable and innovation-driven financial development